Treatment of industrial low grade palm oil via esterification reaction using sonoreactor - Hayyan, Adeeb; Hashim, Mohd Ali; Mirghani, Mohamed Elwathig Saeed; Hayyan, Maan; Alnashef, Inas Muen (The Korean Society of Industrial and Engineering Chemistry., 2014)
In this study, the reduction of free fatty acid (FFA) in low grade palm oil (LGPO) was conducted at various sonication times, ranging from 30 to 300 min. Screening of various acids was reported and selected acid was considered for further study. The results found that strong acids such as sulfuric acid to be superior to other acids. The FFA content of LGPO decreased from 20% to less than 3%, using sulfuric acid at optimum conditions. Treated LGPO can be used as a new type of fuel for various applications such as biodiesel production.